1
$\begingroup$

I was trying to compute the value of $\sum_{n=0}^\infty n(n-1)x^n$ and realizing this is the second derivative of $\sum_{n=0}^\infty x^n = \frac{1}{1-x}$ (whenever $|x|<1$) I proceed to take derivatives. The first derivative of the power series is $$\sum nx^{n-1}=\frac{1}{(1-x)^2}$$

And this is when I get in trouble. Rewriting this last term as $(1-x)^{-2}$, I compute its derivative as $(-2)(1-x)^{-3}(-1)=\frac{2}{(1-x)^3}$, on the other hand $\frac{1}{(1-x)^2} = \frac{1}{(x-1)^2}$ so it seems that the derivative of $(x-1)^{-2}$ is $(-2)(x-1)^{-3}(1)=\frac{-2}{(x-1)^3}$.

While we're at it.... I feel like this "paradox" is probably related to the fact that while $\cos(x)=\cos(-x)$ it is not the case that $(\cos(-x))'=\sin(x)$. I'm not sure how to make sense of this last fact either, but I suspect direct application of the derivative's definition will resolve this .... it is still unsettling.

How can we resolve these paradoxes?

$\endgroup$
  • 3
    $\begingroup$ $\frac{-2}{(x-1)^3}=\frac{2}{-(x-1)^3}=\frac{2}{(-1)^3(x-1)^3}=\frac{2}{(1-x)^3}$ $\endgroup$ – Andrei Feb 19 '17 at 19:38
  • $\begingroup$ Okay. But why is the derivative of $\cos$ not $\sin$? $\endgroup$ – Clclstdnt Feb 19 '17 at 19:39
  • $\begingroup$ And $(\cos(-x))'=(\cos(x))'$ for the same reason, so all is well. $\endgroup$ – Matt Samuel Feb 19 '17 at 19:40
  • $\begingroup$ The derivative of $\cos(x)$ was never $\sin(x)$ in the first place. It's $-\sin(x)$. $\endgroup$ – Matt Samuel Feb 19 '17 at 19:41
  • $\begingroup$ B.t.w. every should know the derivative of $ \dfrac1{x^n}=-\dfrac n{x^{n+1}} $ without having to convert to a negative exponent. $\endgroup$ – Bernard Feb 19 '17 at 19:42
2
$\begingroup$

There are some paradoxes in mathematics, but not in your examples. $$-\frac{2}{(1-x^3)} = \frac{2}{(x^3-1)}$$ And $$(\cos(x))'=-\sin(x)$$ while $$(\cos(-x))'=-\sin(-x)\cdot(-x)'= \sin(-x)=-\sin(x)$$

$\endgroup$
1
$\begingroup$

Consider \begin{align} f(x)&=\frac{1}{(1-x)^2}=(1-x)^{-2} \tag{1}\\ &=\frac{1}{(x-1)^2}=(x-1)^{-2} \tag{2} \end{align} Derivative, first form: $$ f'(x)=-2(1-x)^{-3}(-1)=\frac{2}{(1-x)^3} $$ Second form: $$ f'(x)=-2(x-1)^{-3}(1)=-\frac{2}{(x-1)^3} $$ Since $(1-x)^3=-(x-1)^3$, there's no contradiction nor paradox.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.